Computer simulation studies of roughness of thin films formed in the ion beam assisted deposition (IBAD) process - Oleszkiewicz, Waldemar; Romiszowski, Piotr (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
In this study we present Monte Carlo simulation studies of thin films deposited in the ion beam assisted deposition (IBAD) process. The simulations were performed on a simple cubic lattice with the Metropolis sampling algorithm. Examination of the microstructure and morphology of the simulated film shows that the processes of the surface diffusion of adatoms and the sputtering of the film during its growth as a result of the ion bombardment significantly influence the structure of the deposited layer. The presented simulation model enables one to determine the importance and the influence of these processes on the final structure of the film.
Optica Applicata, Vol. 35, 2005, nr 3, s. 495-501
Keywords: optyka; Monte Carlo simulation; ion beam assisted deposition (IBAD); thin films growth; morphology; roughness